Psychopharmacology of theobromine in healthy volunteers - Baggott, Matthew J. (2013)
BACKGROUND: Theobromine, a methylxanthine related to caffeine and present in high levels in cocoa, may contribute to the appeal of chocolate. However, currently evidence for this is limited. OBJECTIVES: We conducted a within-subjects placebo-controlled study of a wide range of oral theobromine doses (250, 500, and 1000 mg) using an active control dose of caffeine (200 mg) in 80 healthy participants. RESULTS: Caffeine had the expected effects on mood including feelings of alertness, and cardiovascular parameters. Theobromine responses differed according to dose: it showed limited subjective effects at 250 mg and negative mood effects at higher doses. It also dose-dependently increased heart rate. In secondary analyses we also examined individual differences in the drugs' effects in relation to genes related to their target receptors, but few associations were detected. CONCLUSIONS: This study represents the highest dose of theobromine studied in humans. We conclude that theobromine at normal intake ranges may contribute to the positive effects of chocolate, but at higher intakes effects become negative.